IMPLEMENTASI PENDIDIKAN AKHLAK DALAM MEMBENTUK KARAKTER PESERTA DIDIK PADA ERA DIGITAL - Fakri Umar (lembaga Sepercenter, 2026)
The digital age has brought about significant changes in the world of education, including in the development of students’ character. Advances in information technology, social media, and ease of digital access present both opportunities and challenges for the implementation of moral education. Students do not merely interact in physical spaces; they also live in a digital environment that influences their mindset, behaviour, and character development. Therefore, moral education serves as a vital tool in building students’ character so that they can use technology wisely, responsibly, and in accordance with moral and religious values. The various challenges that have emerged include a lack of control over the use of digital media, an increase in individualistic behaviour, cyberbullying, and a crisis of role models in the virtual space. This article employs a literature review approach, analysing various scholarly sources related to moral education, character education, and the development of digital technology. The findings indicate that the implementation of moral education can be achieved through the integration of moral values into learning, the cultivation of positive behaviour, teacher role modelling, collaboration between families and schools, and the utilisation of digital technology as a medium for character development. Ethics education that adapts to technological developments can serve as a solution in shaping students who are not only academically intelligent but also possess strong moral and spiritual integrity.